VD_FINDINFO Arrêt / 2020 / 458 vom 4. Juni 2020 - VD Tribunal cantonal (2020)
DÉCISION DE COTISATIONS, COTISATION AVS/AI/APG, ABSENCE D'ACTIVITÉ LUCRATIVE | 3 LAI, 27 LAPG, 3 al. 1 LAVS, 28 al. 1 RAVS, 28 al. 2 RAVS